Ebola hemorrhagic fever: outbreaks, modeling, and vaccine development - Ahmadi Fard, Ala (Kansas State University, 2016)
Between the years 2014 and 2015, the world experienced a catastrophic outbreak of Ebola virus, which killed over 26,000 people. Several authorities and organizations actively participated in fighting the epidemic. Infectious disease modelers proved to be invaluable towards this goal. This report provides a background on the Ebola epidemic in West Africa and reviews the biological features of the Ebola virus. Moreover, this report applies a new model for Ebola propagation using data collected by the World Health Organization during the span of the outbreak. The model estimates the reproduction number and assesses the role of mitigation strategies in slowing down the progress of the disease. The report also concludes a review of recent advancements in vaccine production against Ebola.
Keywords: Ebola; Computational Epidemiology; Vaccines and Therapeutics; Plan-Based Pharmaceutical